Improvement of agrotechnics of cultivation of table carrot in the conditions of the Volgograd region - B. M. Kizyaev; V. V. Borodychev; A. A. Martynova (Овощи России, 2020)
Relevance. The Volgograd region is one of the major producing regions of table carrots with a difficult climate, therefore, regional adaptation of technology parameters and optimization of reclamation regimes under drip irrigation is necessary. According to most researchers, it is important to take into account the weak development of the root system of carrots in the initial periods of plant growth and development, so the differentiation of the moistened soil layer will allow more rational and productive use of soil moisture.Materials and methods. The working hypothesis of the studies was the assumption that it is possible to intensify the production process of carrots when managing water and mineral nutrition by drip irrigation against the background of high-quality soil preparation with the formation of ridges and the use of modern sowing units. In accordance with the hypothesis put forward, the research program is based on the assessment of threshold values of the conditions for the appointment of vegetation irrigation with drip irrigation and doses of mineral fertilizers.Results. The determination coefficient of the estimated dependences of the carrot water consumption coefficient on the duration of maintaining the starting irrigation regime and mineral nutrition conditions is 0.87-0.94, which characterizes a strong relationship between the indicators included in the equation. it was beneficial for Cordoba F1 hydride to maintain the starting regime of carrot irrigation, oriented to moisten the calculated 0.2-soil layer, to the stage of formation of the 2nd leaf, as well as to apply mineral fertilizers with a dose of N240P90K315 of the planned yield level, 120 t/ha was not received. The productivity of other hybrids studied in the experiment did not exceed 100 t/ha; therefore, it is advisable to introduce mineral fertilizers with a dose of N190P75K245, calculated specifically for this level of planned yield.